Multilayer lead‐free piezoceramic composites: Influence of co‐firing on microstructure and electromechanical behavior. Issue 8 (21st April 2017) - Ayrikyan, Azatuhi; Weyland, Florian; Steiner, Sebastian; Duerrschnabel, Michael; Molina‐Luna, Leopoldo; Koruza, Jurij; Webber, Kyle G.
Abstract: In this study lead‐free 2‐2 and 0‐3 ceramic/ceramic composites comprised of the non‐ergodic relaxor 0.93(Bi1/2 Na1/2 )TiO3 –0.07BaTiO3 and ergodic relaxor 0.94Bi0.5 (Na0.75 K0.25 )0.5 TiO3 –0.06BiAlO3 were investigated. The macroscopic electromechanical behavior was characterized as a function of continuent content, revealing an enhancement in the unipolar strain from the multilayer composite structure. Systematic evaluation of the effects of co‐sintering on microstructural properties, such as grain size and porosity, revealed potential mechanisms by which the increase in unipolar strain was achieved. In addition, interdiffusion between the constituents was observed, providing evidence for the formation of a functionally graded ceramic by co‐sintering. These data are contrasted with high‐resolution energy dispersive X‐ray microanalysis for measurement of chemical composition across the interface of 2‐2 ceramics. These findings provide insight into how synthesis routes can be optimized for tailoring the enhancement of electromechanical properties of lead‐free electroceramic composite systems.